Does Smokers' Self-Construal Moderate the Effect of (Self-)persuasion on Smoking?. (5th February 2019) - Li, Shuang; Ritter, Simone M.; Bi, Chongzeng; van Baaren, Rick; Müller, Barbara C. N.
Research has shown that self-persuasion is more effective in increasing smokers' risk perception and decreasing short-term smoking behavior compared to the traditional direct persuasion. However, the role of self-construal, which is closely associated with how one perceives persuasive messages, is not explored. The current research filled this gap by introducing self-construal to the self-persuasion literature to investigate its potential moderating role. Throughout five studies, we measured daily smokers' chronic self-construal (Study 1–3), selected smokers with different culturally-nurtured self-construal (Study 4), and primed situational self-construal (Study 5) to examine the role of self-construal in regard to smokers' cognition, attitude, and short-term smoking behavior, after being targeted by direct- or self-persuasion. Health warnings on cigarette packages and text regarding the negative consequences of smoking were used as direct persuasive messages. Adapted versions of health warnings and an argumentation task were used to induce self-persuasion. Null results were obtained from most of the studies. The overall support for the null hypothesis, however, remains weak and needs to be further verified. Limitations and future research direction are discussed.